What information do healthcare professionals need to inform premenopausal women about risk-reducing salpingo-oophorectomy?. Issue 1 (January 2020) - Hickey, Martha; Rio, Ines; Trainer, Alison; Marino, Jennifer L; Wrede, C. David; Peate, Michelle
Abstract: Objective: The aim of this study was to identify the unmet information needs of healthcare professionals managing risk-reducing bilateral salpingo-oophorectomy (RRBSO) in premenopausal women. Methods: A cross-sectional survey of healthcare professionals managing high-risk women in Victoria, Australia. Questions included roles and responsibilities around RRBSO, perceived barriers to uptake of RRBSO, and unmet information needs. Results: One hundred eighteen healthcare professionals across 10 different disciplines and specialties were approached to participate, of whom 47 completed the survey. Most respondents were genetic counselors (47%) or nurses (19%) and all worked in the public health system. Almost all (81%) provided information about RRBSO, but there was considerable uncertainty about who was responsible for making decisions with high-risk women about RRBSO. Most (85%) were "quite a bit" or "extremely" confident about informing high-risk women about ovarian cancer risk reduction from RRBSO and the surgical procedure (47%), but only one-third were "quite a bit" or "extremely" confident about discussing (36%) or managing (31%) surgical menopause. Furthermore, surgical menopause was considered the main barrier (88%, "quite a bit" or "extremely") to RRBSO. Most healthcare professionals (78%) wanted more information and resources about surgical menopause for high-risk women. Conclusions: There is uncertainty around the roles and responsibilities of healthcare professionals managing high-risk women around RRBSO. Surgical menopause is perceived as a major barrier to RRBSO and healthcare professionals lack confidence in managing this outcome. N/A: Video Summary: http://links.lww.com/MENO/A477 . Abstract : Supplemental Digital Content is available in the text